Coulombic Fluids Bulk and Interfaces - Freyland, Werner (Springer Series in Solid-State Sciences,, 2011)
Ionic liquids have attracted considerable interest in recent years. In this book the bulk and interfacial physico-chemical characteristics of various fluid systems dominated by Coulomb interactions are treated which includes molten salts, ionic liquids as well as metal-molten salt mixtures and expanded fluid metals. Of particular interest is the comparison of the different systems. Topics in the bulk phase concern the microscopic structure, the phase behaviour and critical phenomena, and the metal-nonmetal transition. Interfacial phenomena include wetting transitions, electrowetting, surface freezing, and the electrified ionic liquid/ electrode interface. With regard to the latter 2D and 3D electrochemical phase formation of metals and semi-conductors on the nanometer scale is described for a number of selected examples. The basic concepts and various experimental methods are introduced making the book suitable for both graduate students and researchers interested in Coulombic fluids.